Perlindungan Hukum Kreditor yang Tidak Mendaftarkan Tagihan terhadap Klausul Perjanjian Perdamaian yang Mengakibatkan Penghapusan Piutang : Studi Kasus Putusan Homologasi Nomor 62/Pdt.Sus-PKPU/2021/PN Niaga Sby - Kartika Eka Pertiwi; Sudaryat Sudaryat; Ema Rahmawati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The Suspension of Debt Payment Obligations (PKPU) is a rehabilitative mechanism, but it is susceptible to bad faith abuse. This case study examines Homologation Decision No. 62/Pdt.Sus-PKPU/2021/PN Niaga Sby, where judges ratified a composition plan creating a "Previous Trade Creditors" category. This clause, targeting unregistered creditors, effectively resulted in a 95% debt write-off, injuring the Principle of Justice. This research aims to analyze the judges' legal considerations in ratifying this clause and examines their failure to apply material judicial obligations regarding the debtor's bad faith. This research utilizes a normative juridical method with a statute and case study approach. The analysis is qualitative, examining the decision and relevant legislation, supplemented by an interview with a practicing Commercial Court judge. The primary finding is that the judges' considerations were overly positivistic, focusing only on the formal voting quorum (Article 281, UU KPKPU). They failed to execute their imperative duty under Article 285(2)(c) to reject a plan achieved via "dishonest means". The 95% write-off is prima facie bad faith and is punitive, not rehabilitative. The judges misinterpreted the Publicity Principle; non-registration should only cause the loss of voting rights (procedural), not the loss of claim rights (substantive). This failure of material judicial review legitimized the abuse of the PKPU institution.